2020
DOI: 10.1103/physrevresearch.2.013367
|View full text |Cite
|
Sign up to set email alerts
|

Surface states and arcless angles in twisted Weyl semimetals

Abstract: Fermi arc states are features of Weyl semimetal (WSM) surfaces which are robust due to the topological character of the bulk band structure. We demonstrate that Fermi arcs may undergo profound restructurings when surfaces of different systems with a well-defined twist angle are tunnel-coupled. The twisted WSM interface supports a moiré pattern which may be approximated as a periodic system with large real-space unit cell. States bound to the interface emerge, with interesting consequences for the magneto-oscil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…To set the notation for the interface states of two twisted WSMs, we briefly review the derivation of the surface states for a semi-infinite WSM 34 . We begin with a general two band lattice model of a time reversal symmetry broken WSM on a cubic lattice.…”
Section: Time-reversal Symmetry Broken Model Of a Wsm And Its Surface...mentioning
confidence: 99%
See 1 more Smart Citation
“…To set the notation for the interface states of two twisted WSMs, we briefly review the derivation of the surface states for a semi-infinite WSM 34 . We begin with a general two band lattice model of a time reversal symmetry broken WSM on a cubic lattice.…”
Section: Time-reversal Symmetry Broken Model Of a Wsm And Its Surface...mentioning
confidence: 99%
“…To find the surface states, following Ref. 34, we assume that the slab is semi-infinite in the z-direction, with lattice sites labeled by n = 0, 1, 2 . .…”
Section: Time-reversal Symmetry Broken Model Of a Wsm And Its Surface...mentioning
confidence: 99%
“…Most experiments on Weyl semimetals focus on the angle-resolved photoemission spectroscopy, in which the existence of FAs has been confirmed. There are also theoretical studies of the FA and its transport properties [40][41][42][43][44], like quasiparticle interference (QPI) [45,46]. Recent progress has also shown that the configurations of the FAs are sensitive to the details of the sample boundary [47][48][49], thus opening the possibility for engineering FAs and exploring their novel effects and potential applications through surface device fabrication and transport measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The gapless bulk Weyl nodes must coexist on general grounds with gapless and topologically protected Fermiarc surface states, which connect the projections on the surface Brillouin zone of different Weyl nodes. These surface states are chiral, i.e., have a unidirectional sense of propagation, and define open curves as Fermi surface segments [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The Fermi arc parts of the Fermi surface seamlessly merge with the bulk quasiparticle parts at the arc termination points [6,23,35,36].…”
Section: Introductionmentioning
confidence: 99%